2018
DOI: 10.1371/journal.pone.0202828
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma asperelloides ethanolic extracts efficiently inhibit Staphylococcus growth and biofilm formation

Abstract: Fungi from the widely distributed genus Trichoderma are of great biotechnological interest, being currently used in a vast range of applications. Here, we report that high-molecular weight fraction (HWF) derived from Trichoderma asperelloides ethanolic extract exhibits antibiotic activity against staphylococcal biofilms. The antibacterial and anti-biofilm properties of T. asperelloides extracts were evaluated by well-established assays in Staphylococcus aureus ATCC strains (29213 and 6538) and in one clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We have previously shown that an in vivo treatment of cerebral malaria with the ethanolic extract of Trichoderma stromaticum has promising effects, including reduction of parasitemia and inflammation, increased survival, and prevention of neurological signs of cerebral malaria in C57BL/6 mice (Cariaco et al, 2018 ). In a similar way, the use of crude ethanolic extracts of T. asperelloides and its fraction can efficiently inhibit Staphylococcus growth and biofilm formation, representing a candidate for the development of new antibiotics against gram-positive bacteria (Santos et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that an in vivo treatment of cerebral malaria with the ethanolic extract of Trichoderma stromaticum has promising effects, including reduction of parasitemia and inflammation, increased survival, and prevention of neurological signs of cerebral malaria in C57BL/6 mice (Cariaco et al, 2018 ). In a similar way, the use of crude ethanolic extracts of T. asperelloides and its fraction can efficiently inhibit Staphylococcus growth and biofilm formation, representing a candidate for the development of new antibiotics against gram-positive bacteria (Santos et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For bacteria, a previous study revealed that endophytic fungal extract, Trichoderma asperelloides affected bacterial cells by inducing cellular damages including cell wall and cytoplasmic membrane disturbance. 60 Besides, Yenn 61 suggested that the mode of action of endophytic fungal extract, Penicillium purpurogenum ED76 causes significant damage to bacterial cells including invaginations of the cell wall. As for yeast, the majority of the previous studies observed the fungal extracts affected the fungal cell wall and membrane structures.…”
Section: Discussionmentioning
confidence: 99%
“…The mature biofilm test was performed following Santos et al (2018) method. For that, 200 µL of 24 h bacteria cultured in BHI were seeded in 96 microwell plates.…”
Section: Biofilm Biomass Inhibitionmentioning
confidence: 99%